Spectral curves of surface reflectance in some antarctic regions - Lupi, A.; Tomasi, C.; Orsini, A.; Cacciari, A.; Vitale, V.; Georgiadis, Teodoro; Casacchia, Ruggero; Salvatori, Rosamaria; Salvi, S. (Societa italiana di fisica, 2001)
Four surface reflectance models of solar radiation were determined by examining several sets of field measurements taken for clear-sky conditions at various sites in Antarctica. Each model consists of the mean spectral curve of surface reflectance in the 0.25–2.7 μm wavelength range and of the dependence curve of total albedo on the solar elevation angle h, within the range from 5◦ to 55◦. The TNB (Terra Nova Bay) model refers to a rocky terrain where granites are predominant; the NIS (Nansen Ice Sheet) model to a glacier surface made uneven by sastrugi and streaked by irregular fractures; the HAP (High Altitude Plateau) model to a flat ice surface covered by fresh snow and scored by light sastrugi; and the RIS (Ross Ice Shelf) model to an area covered by the sea ice pack presenting many discontinuities in the reflectance features, due to melt water lakes, puddles, refrozen ice and snow pots. The reflectance curve obtained for the TNB model presents gradually increasing values as wavelength increases through the visible spectral range and almost constant values at infrared wavelengths, giving a total albedo value equal to 0.264 at h = 30◦, which increases by about 80% through the lower range of h and decreases by 12% through the upper range. The reflectance curves of the NIS, HAP and RIS models are all peaked at visible wavelengths and exhibit decreasing values throughout the infrared spectral range, giving values of total albedo equal to 0.464, 0.738 and 0.426 at h = 30◦, respectively. These values were estimated to increase by 8–14% as h decreases from 30◦ to 5◦ and to decrease by 2–4% only as h increases from 30◦ to 55◦.